Analisis Studi Kelayakan Bisnis Pada Usaha Kedai DimsumKu - Mila Salbiyah; Farhan Mukti Mutakin; Rafli Maulana Yusuf; Perwito Perwito (CV. ITTC INDONESIA, 2025)
This study aims to analyze the feasibility of the dimsum business with a comprehensive approach, including legal aspects, market and marketing aspects, technical aspects, management and organizational aspects, and financial aspects. In terms of market and marketing, this study identifies target segments, effective marketing strategies, and competitor analysis to determine the optimal market position. The technical aspects include the selection of strategic locations, the necessary facilities, and efficient production processes to ensure product quality. On the management and organizational side, this research discusses the organizational structure, the role of human resources, and the management system needed to support store operations. Finally, financial analysis is carried out to compile income and expense projections, calculate break-even points, and explore potential sources of financing. The results of this analysis show that the dimsum shop business has good potential to grow and provide profits, as long as it is managed properly and takes into account all aspects that have been analyzed